Boosting Sulfonylation Reactions between Vinyl Triflates and Alkenes toward β-Ketosulfones Using Aqueous Sulfurous Acid - Kawamoto, Takuji; Takeda, Yuki; Kawabata, Takahiro; Kamimura, Akio (Synthesis, 2024)
We successfully synthesized trifluoromethylated β-ketosulfones via the reaction of vinyl triflates with alkenes employing aqueous sulfurous acid as an external source of SO2. The PhSSPh/photoinitiated reaction with vinyl triflates that contain electron-deficient groups or halogens did not show any base-related effects, whereas the radical reaction was impeded in the absence of a base in the case of vinyl triflates generated from phenylacetylenes.
Keywords: radicals; trifluoromethylation; sulfonylation; vinyl triflates; β-ketosulfones; sulfurous acid